Effect of Different Methods of Induction on the Mode of Delivery and Fetal Outcome - Buhari, Nabila Aminu; Ahmed, Sumayya Lugman; Sohrabi, Nastaran Redha; Ogunsola, Hidayat Yetunde; Shaikh, Riwana B; Sharbatti, Shatha Al; Mathew, Elsheba (Bangladesh Journal of Obstetrics & Gynaecology, 2013)
Objectives: To study various methods of induction of labor and their effect on mode of delivery and fetal outcome. Methods: 104 pregnant women induced in Gulf Medical College hospital from August to November 2009 were included. Mothers were observed from the start of their induction and followed up till they were discharged. The methods of induction compared were the use of prostaglandin, oxytocin, prostaglandin and oxytocin combined and artificial rupture of membranes. Results: Out of 104 pregnant women, 86 (89%) had normal vaginal delivery. Of these, 36 (41.9%) were induced with combination of prostaglandin and oxytocin, 32 (37.2%) with prostaglandin, 14 (16.2%) with oxytocin, and 4 (4.6%) with artificial rupture of membranes. 13 (12.5%) mothers delivered through caesarean section of these, 7 (53.8%) mothers were induced with prostaglandin, 3 (23%) with prostaglandin and oxytocin, 2 (15.3%) with oxytocin alone, and 1 (7.7%) with artificial rupture of membranes. Induction of labor with combination of prostaglandin and oxytocin was found to be the most effective method. Duration of labor between primigravidas and multigravidas were significantly different with primigravidas having longer duration of labor with mean time of 12.47 hours while multigravidas had 9.16 hours. Conclusion: Induction of labor with combination of prostaglandin and oxytocin was found to be the most effective method in this study with very good progressing to normal vaginal delivery. Further research is needed on a larger scale to compare other methods of labor induction on parturient to be able to recommend the most effective method of labor induction. DOI: http://dx.doi.org/10.3329/bjog.v26i2.13785 Bangladesh J Obstet Gynaecol, 2011; Vol. 26(2) : 81-85